PERSPEKTIF HUKUM PERJANJIAN INTERNASIONAL ATAS KORBAN PENDUDUK SIPIL PADA KONFLIK BERSENJATA DI REPUBLIK DEMOKRATIK KONGO: PERSPECTIVE OF INTERNATIONAL TREATIES ON VICTIMS OF CIVILIAN POPULATIONS OF ARMED CONFLICT IN DEMOCRATIC REPUBLIK OF THE CONGO - Andienda, Syarifah Prasya; Sekariani, Azizah; Fitriliani, Yulia (Fakultas Hukum Universitas Trisakti, 2024)
This study aims to analyze the reparation mechanisms available to victims of international crimes, particularly in the context of a convicted person's inability to fulfill financial obligations, as well as the involvement of states pursuant to Article 31 of the ARSIWA. The case of Germain Katanga in the Democratic Republic of the Congo serves as a concrete example in which the defendant was found guilty of war crimes and crimes against humanity, yet lacked the means to provide direct compensation to the victims. Applying a normative legal approach, this research examines key instruments of international law, including the 1998 Rome Statute, the 1949 Geneva Conventions, the 1977 Additional Protocols, and the 1969 Vienna Convention on the Law of Treaties. The findings demonstrate that the Trust Fund for Victims (TFV), as established under Article 79 of the Rome Statute, functions as a collective mechanism that ensures victims' rights to reparation when the convicted person is unable to pay. Furthermore, Article 31 of the ARSIWA affirms the obligation of states to guarantee the fulfillment of reparation duties, either by contributing to the TFV or by supporting decisions rendered by the International Criminal Court (ICC). This study recommends strengthening international cooperation to ensure that the principle of restorative justice for victims continues to be upheld within the framework of international law.